TENSILE STRENGTH STUDY OF HYBRID POLYESTER COMPOSITE MATERIAL REINFORCED WITH PINEAPPLE LEAF FIBER AND CARBON FIBER - Nugroho, Suksma Cahyo Aji; Wulansari, Ajeng; Irfansyah, Ade (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
Composites are materials made of two or more different components, which are combined to create superior or specific properties. Composite materials usually consist of a matrix and reinforcement. This research aims to study the effect of changing the number of layers on the tensile strength of pineapple leaf fiber composites and carbon fiber composites. Pineapple leaf fiber composite is a potentially environmentally friendly material, while carbon fiber is known for its high durability. This research uses experimental research methods. The composite was made with a glass mold size of 170 x 90 x 3 mm for tensile testing by molding a mixture of resin and fiber. This research combines natural fibers and synthetic fibers with testing standards using ASTM D638 for tensile tests. The variables used are 1 carbon fiber, 1 pineapple leaf fiber, 1 carbon fiber; 1 carbon fiber, 2 pineapple leaf fibers, 1 carbon fiber; and 2 carbon fibers, 1 pineapple leaf fiber, 2 carbon fibers. Performed alkalization treatment to pineapple leaf fibers by soaking in 5% NaOH solution for 2 hours. The final result of the research conducted was to obtain the tensile strength results of each specimen, by obtaining the maximum tensile strength of the specimen of 152.47 Mpa and the highest strain value of 0.130267%. For the results of the lowest elastic modulus value of 3600,713 Mpa and the highest value of 9613,392 Mpa.